1999
DOI: 10.1111/j.1469-445x.1999.tb00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of contractile and elastic properties of rat soleus muscle fibres under unloading conditions

Abstract: S U M M A R YRats were submitted to 14 days of hindlimb suspension in order to examine the contractile and elastic properties of the soleus muscles under disuse conditions. The calcium/strontium activation properties, the maximal shortening velocity ( V J , as well as the time behaviour of force transients following quick releases and the T, curves characterizing the active part of the s8eries elastic elements, were determined on single chemically skinned fibres. After the functional measurements, the fibres w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
(35 reference statements)
4
21
0
Order By: Relevance
“…A decrease in the stiffness of isolated soleus muscle (Canon and Goubel 1995) and in Achilles tendon stiffness (Almeïda-Silveira et al 2000) was observed after 3 wk of unloading. The results obtained by Canon and Goubel (1995) were confirmed by Toursel et al (1999) on isolated skinned fibers of rat soleus muscle. Moreover, the passive tension of in situ rat soleus muscle increased after 7 and 14 days of whole body suspension (Gillette and Fell 1996).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…A decrease in the stiffness of isolated soleus muscle (Canon and Goubel 1995) and in Achilles tendon stiffness (Almeïda-Silveira et al 2000) was observed after 3 wk of unloading. The results obtained by Canon and Goubel (1995) were confirmed by Toursel et al (1999) on isolated skinned fibers of rat soleus muscle. Moreover, the passive tension of in situ rat soleus muscle increased after 7 and 14 days of whole body suspension (Gillette and Fell 1996).…”
Section: Introductionsupporting
confidence: 71%
“…These fibers are less stiff than the slow type I fibers (Petit et al 1990). After HH, in rat soleus muscle, Toursel et al (1999) also reported an increase in the compliance on a population of hybrid fast fibers, which coexpressed the MHC IIA and MHC I isoforms (MHC IIA Ͼ MHC I). Moreover, Miller et al (2001) have demonstrated that HH induced a shift in the relative proportion of collagen isoform (type I to III) in the soleus muscle in relation to the fiber type transition (slow to fast).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no one has raised the question of investigating changes in the stiffness properties of muscle fibres following high-intensity resistance training in elderly individuals. Nevertheless, it is well known that muscle fibres, which have different contractile properties such as unloaded shortening velocity, may well also have different stiffness properties (Toursel et al 1999). In fact, according to Toursel et al (1999), fast-twitch fibres may have a bigger unloaded shortening velocity and may be less stiff than slow-twitch fibres.…”
Section: Mt Stiffness and Trainingmentioning
confidence: 98%
“…Unfortunately, no one has raised the question of investigating changes in the stiffness properties of muscle fibres following training in old age. Nevertheless, it is well known that muscle fibres, which have different contractile properties, may well also have different stiffness properties (Toursel et al 1999). In fact, according to Toursel et al (1999) type IIa fibres may have a bigger specific force and may be less stiff than type I fibres.…”
Section: Elastic Properties Of the Mt Systemmentioning
confidence: 98%